Long-term performance of a microbial electrolysis cell operated with periodic disconnection of power supply. Issue 30 (8th May 2018) - Hussain, S. A.; Perrier, M.; Tartakovsky, B.
Abstract : This study describes a new approach for achieving stable long-term performance and maximizing removal of chemical oxygen demand (COD) in a Microbial Electrolysis Cell (MEC) by periodic disconnection of the MEC power supply. Abstract : This study describes a new approach for achieving stable long-term performance and maximizing the removal of chemical oxygen demand (COD) in a Microbial Electrolysis Cell (MEC). In the proposed approach, the MEC power supply is periodically disconnected, e.g. at a frequency of 0.1–0.5 Hz and a duty cycle of 90–95%. To evaluate the impact of such periodic power supply disconnection (on/off mode) on MEC performance, experiments were carried out in two flow-through MECs with activated granular carbon electrodes. The on/off operating strategy was applied to one MEC, while the other one was operated at a fixed voltage (control MEC). Long-term on/off operation resulted in progressive increase in COD removal efficiency (from 80% to 90%) and MEC current over time, while the control MEC showed stable but inferior performance. Furthermore, by changing the operating strategies and applying the on/off approach to the control MEC, its COD removal was increased from 78% to 83% and internal resistance decreased. The proposed on/off mode of operation can be used to develop a high-rate MEC-based wastewater treatment system.